2016
DOI: 10.1126/scitranslmed.aad9704
|View full text |Cite
|
Sign up to set email alerts
|

The BACE1 inhibitor verubecestat (MK-8931) reduces CNS β-amyloid in animal models and in Alzheimer’s disease patients

Abstract: β-Amyloid (Aβ) peptides are thought to be critically involved in the etiology of Alzheimer's disease (AD). The aspartyl protease β-site amyloid precursor protein cleaving enzyme 1 (BACE1) is required for the production of Aβ, and BACE1 inhibition is thus an attractive target for the treatment of AD. We show that verubecestat (MK-8931) is a potent, selective, structurally unique BACE1 inhibitor that reduced plasma, cerebrospinal fluid (CSF), and brain concentrations of Aβ40, Aβ42, and sAPPβ (a direct product of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
338
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(365 citation statements)
references
References 43 publications
9
338
0
Order By: Relevance
“…Verubecestat (MK-8931) and Lanabecestat (AZD3293) are two representative BACE1 inhibitors under clinical trials. Although phase I and phase II data present exciting benefits on AD models, the preliminary results of phase III trial have failed to meet clinical significance for Verubecestat [324, 325]. Nevertheless, the other oral BACE1 inhibitor Lanabecestat has recently gained support from FDA to further expand its phase III trial, following the data analysis based on early results [326].…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…Verubecestat (MK-8931) and Lanabecestat (AZD3293) are two representative BACE1 inhibitors under clinical trials. Although phase I and phase II data present exciting benefits on AD models, the preliminary results of phase III trial have failed to meet clinical significance for Verubecestat [324, 325]. Nevertheless, the other oral BACE1 inhibitor Lanabecestat has recently gained support from FDA to further expand its phase III trial, following the data analysis based on early results [326].…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…This is particularly interesting as BACE inhibitors are actively being explored as a therapeutic strategy in AD (Kennedy, et al 2016). Our detection of BACE2 in α cells is in contrast to reports indicating the highest pancreatic BACE2 expression is found within pancreatic β cells (Esterhazy et al 2011; Finzi, et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the high potency of BACE inhibitors in reducing brain Aβ levels (30), several compounds are currently either in preparation for or in use in clinical trials. Although these ongoing clinical trials have not reported any major safety issues so far, there remain some concerns about potential (and perhaps subtler) side effects.…”
Section: Discussionmentioning
confidence: 99%